Optimization of grouting reinforcement performance of superfine sulfoaluminate cement composite system - Pengfei WANG; Pengyun YAN; Mingxuan ZHANG (Meitan kexue jishu)
Aiming at the technical demands for the control of the stability of the surrounding rock of the underground roadway in coal mines and the improvement of the effect of grouting reinforcement, and with the target orientation of the resource utilization of industrial solid wastes and the reduction of the cost of grouting, we have systematically carried out the research on the modification of the admixture of the composite cementitious material system of ultrafine fly ash (UFA) and ultrafine sulfated aluminate cement (USC).Through the introduction of water-reducing components such as polycarboxylic acid water-reducing agent (PCE) and naphthalene water-reducing agent (FDN), combined with β-cyclodextrin (β-CD), citric acid (CA) and other retarding regulators, the synergistic influence mechanism of single-mixing and compound-mixing modes of admixtures on the performance of grouting materials of the composite system has been investigated in depth. By combining macro performance test and micro structure characterization, the development of slurry fluidity, coagulation and hardening characteristics and mechanical strength were comprehensively evaluated, and the evolution of hydration products and performance regulation mechanisms were revealed through XRD, SEM and other analytical means, and the optimization effect of the materials was finally verified through the downhole grouting project.The experimental results show that: ① The type of water-reducing agent has a significant role in regulating the performance of the material: when the dosage of PCE is 0.6%, the 28 d compressive strength of the grouting material is the highest and shows a continuous growth trend, with the highest increase of 20.27%; while the strength inflection point of FDN occurs when the dosage of FDN is 0.3%, and the excessive dosage (>0.6%) leads to the decrease of strength. Both water-reducing agents can effectively improve the slurry fluidity and prolong the setting time; ② The synergistic effect of retarder and water reducer shows differences: the introduction of 0.2% β-CD in PCE-modified system can make the compressive strength increase by 6.90%−17.18%, but more than the critical dosage of excessive retarder leads to strength attenuation; while the FDN system is compounded by CA dosing, the strength shows a monotonous decreasing trend with the increase of dosage, and the dosage of 0.6% CA dosage causes the strength loss of about 13.78%; fixing the dosage of the two water-reducing agents, with the addition of the corresponding retarder from 0 to 0.6%, the setting time of the grouting material is gradually extended, and the flow degree shows a high and then low change; ③ Microstructure analysis reveals that the water-reducing agent optimizes the morphology of caliche AFt through the regulation of the environment, and the retarding agent promotes the filling of pores with gel by retarding hydration, and the synergistic effect of the two inhibits the transformation of AFt to monosulfide type to a certain extent. The two synergistic effects inhibit to some extent the transformation of AFt to monosulfide-type hydrated calcium sulfoaluminate (AFm); ④ The field industrial test shows that the optimized UFA-USC composite slurry in the roadway grouting, the peripheral rock deformation is significantly reduced, and the amount of top and bottom slabs and two gangs approaching have been effectively controlled, to maintain the shape of the roadway section, and to achieve a better reinforcing effect.